Manajemen Pondok Pesantren Baitul Akbar Babadan Pangkur Ngawi Dalam Meningkatkan Kemampuan Tahfizd Qur’an Santri - Ni’matul Ulya Rohmatul Azizah; Luluk Muasomah; Hanifah Hikmawati (Inisiasi : Jurnal Manajemen Pendidikan Islam, 2022)
Baitul Akbar Islamic Boarding School is an educational institution of the Qur'an with salafi education programs and kholafi, diniyah and tahfizh education programs. The purposes of this study were 1) to determine the implementation of Baitul Akbar Islamic boarding school management, 2) To determine the ability of Baitul Akbar Islamic boarding school students to memorize the Al Quran, 3) To determine the management of Baitul Akbar Islamic boarding school in improving the ability to memorize Al Quran Santri. This study uses a qualitative approach with a descriptive method, where data is collected by means of observation, interviews and documentation. The analysis technique of this research is through the stages of data reduction, data presentation and conclusion drawing. The results of this study are: 1) The management of the Baitul Akbar Islamic boarding school is carried out in planning, organizing, directing, monitoring and evaluating stages. 2) The ability of students to memorize the Koran in general is getting stronger with murajah. 3) The management of the Baitul Akbar Islamic boarding school is able to improve the ability of students to memorize the Qur'an.